Art culture of avant-guarde in a context of development of communicative skill’s of the future teachers of art - Vlasenko, I.M. (Pedagogy of Higher and Secondary Education, 2006)
In the article communicative skills of the future teachers of art are classified from positions of the semiotics approach. The model of communicative skills concerning vanguard culture is developed by levels, fundamental characteristics of avant-guarde are revealed.